Distribution and antibiotic resistance profile of key Gram-negative bacteria that cause community-onset urinary tract infections in the Russian Federation: RESOURCE multicentre surveillance 2017 study. (June 2020) - Rafalskiy, Vladimir; Pushkar, Dmitry; Yakovlev, Sergey; Epstein, Oleg; Putilovskiy, Mikhail; Tarasov, Sergey; Glazunov, Alexey; Korenev, Sergeiy; Moiseeva, Ekaterina; Gorelysheva, Natalia
Highlights: Urinary tract infections are common in clinical practice in the Russian Federation. Escherichia coli ( E. coli ) was the most commonly isolated uropathogen (49.1%). Up to 50% of the E. coli strains were resistant to ampicillin and co-trimoxazole. E. coli were highly susceptible to imipenem, nitrofurantoin and fosfomycin. Abstract: Background: Urinary tract infections (UTIs) are among the most common bacterial infections in clinical practice. This RESOURCE (pathogen distribution and antibiotic RESistance prOfile of key Gram-negative bacteria caUsing community-onsEt URinary traCt) study aimed to determine the antimicrobial resistance profile of Gram-negative bacteria isolated from outpatient urine samples collected across the Russian Federation. Methods: A total of 96 781 urine samples were collected from 520 cities in the Russian Federation between 01 January 1 and 31 December 2017. Antibiotic susceptibility was performed using semi-automated analysers. The mean age of the study population was 40.9 years; 80.2% were female and 19.8% were male. Results: Of the uropathogens that were isolated, 64.2% were Gram-negative bacteria. Among these, Escherichia coli ( E. coli ) was the most common (49.1%) followed by Klebsiella pneumoniae (9.5%), Proteus mirabilis (2.9%), Pseudomonas aeruginosa (1.7%), and Enterobacter spp. (1.0%). Of the antibiotics that were tested, 50% of the isolated E. coli strains were resistant to ampicillin, 30.3% to co-trimoxazole, 26.2% to aztreonam, 28.8% to levofloxacin, and 21% to cefuroxime. Conversely, E. coli was highly susceptible to imipenem (0.7% resistant strains isolated), amikacin (0.9%), nitrofurantoin (4.5%), and fosfomycin (1.2%). The most active antimicrobials against Klebsiella pneumoniae were imipenem (6.8% resistant strains) and colistin (0.5%), while piperacillin/tazobactam (4.2%), cefoperazone/sulbactam (3.1%) and imipenem (0%) were the most active agents against Proteus mirabilis . The antimicrobials showing the highest activity against Pseudomonas aeruginosa were colistin (10.7% resistant strains) and aztreonam (0%), while piperacillin/tazobactam (7.1%) and cefoperazone/sulbactam (2.3%) showed the highest activity against Enterobacter spp. Conclusion: The prevalence of fluoroquinolone and cephalosporin resistance among common UTI-causing Gram-negative bacteria highlights the growing challenge of successfully treating community-onset UTIs.